3-Oxoisoxazole-2(3H)-carboxamides and isoxazol-3-yl carbamates: Resistance-breaking acetylcholinesterase inhibitors targeting the malaria mosquito, Anopheles gambiae. Issue 6 (15th March 2015) - Verma, Astha; Wong, Dawn M.; Islam, Rafique; Tong, Fan; Ghavami, Maryam; Mutunga, James M.; Slebodnick, Carla; Li, Jianyong; Viayna, Elisabet; Lam, Polo C.-H.; Totrov, Maxim M.; Bloomquist, Jeffrey R.; et al.
Graphical abstract: Abstract: To identify potential selective and resistance-breaking mosquitocides against the African malaria vector Anopheles gambiae, we investigated the acetylcholinesterase (AChE) inhibitory and mosquitocidal properties of isoxazol-3-yl dimethylcarbamates (15 ), and the corresponding 3-oxoisoxazole-2(3 H )-dimethylcarboxamide isomers (14 ). In both series, compounds were found with excellent contact toxicity to wild-type susceptible (G3) strain and multiply resistant (Akron) strain mosquitoes that carry the G119S resistance mutation of AChE. Compounds possessing good to excellent toxicity to Akron strain mosquitoes inhibit the G119S mutant of An. gambiae AChE ( Ag AChE) with k i values at least 10- to 600-fold higher than that of propoxur, a compound that does not kill Akron mosquitoes at the highest concentration tested. On average, inactivation of WT Ag AChE by dimethylcarboxamides14 was 10–20 fold faster than that of the corresponding isoxazol-3-yl dimethylcarbamates15 . X-ray crystallography of dimethylcarboxamide14d provided insight into that reactivity, a finding that may explain the inhibitory power of structurally-related inhibitors of hormone-sensitive lipase. Finally, human/ An. gambiae AChE inhibition selectivities of these compounds were low, suggesting the need for additional structural modification.